Critical perspectives on plurilingualism in deaf education - Snoddon, Kristin; Weber, Joanne, 1959- (Bristol, UK ; Blue Ridge Summit, PA : Multilingual Matters, 2021)
"This book is the first edited international volume focused on critical perspectives on plurilingualism in deaf education, which encompasses education in and out of schools and across the lifespan. It explores issues such as bimodal bilingualism, translanguaging, teacher education, sign language interpreting and parent sign language learning"--
Frontmatter -- Contents -- Contributors -- Foreword -- Introduction: Plurilingualism and (In)competence in Deaf Education -- Part 1: Plurilingual Language Planning in Deaf Education -- 1 Four Decades of Sign Bilingual Schools in Sweden: From Acclaimed to Challenged -- 2 Sign Language Planning and Policy in Ontario Teacher Education -- 3 Bourdieu, Plurilingualism and Sign Languages in the UK -- 4 Plurilingualism in Deaf Education in France: Language Policies, Ideologies and Practices for the Bimodal Bilingual Skills of Deaf Children -- 5 Plurilingualism and Policy in Deaf Education -- Part 2: Plurilingual Education Practices and Models -- 6 Sign Bilingualism as Semiotic Resource in Science Education: What Does It Mean? -- 7 Bimodal Bilingual Programming at a Canadian School for the Deaf -- 8 Implementing a New Design in Parent Sign Language Teaching: The Common European Framework of Reference for Languages -- 9 Family Language Policy and Planning: Families with Deaf Children -- 10 Critical Perspectives on Education Mediated by Sign Language Interpreters: Inclusion or the Illusion of Inclusion? -- Index
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on July 23, 2021).
JSTOR
Keywords: Deaf people -- Education; Multilingualism; Multilingual communication; Multilingual education; Deafness; Education; Multilingualism; Personnes sourdes -- Éducation.; Multilinguisme; Communication multilingue; Enseignement multilingue; LANGUAGE ARTS & DISCIPLINES / Sign Language; Deaf -- Education; Multilingual communication; Multilingual education; Multilingualism